2016
DOI: 10.1371/journal.pone.0165669
|View full text |Cite
|
Sign up to set email alerts
|

Material Properties from Air Puff Corneal Deformation by Numerical Simulations on Model Corneas

Abstract: ObjectiveTo validate a new method for reconstructing corneal biomechanical properties from air puff corneal deformation images using hydrogel polymer model corneas and porcine corneas.MethodsAir puff deformation imaging was performed on model eyes with artificial corneas made out of three different hydrogel materials with three different thicknesses and on porcine eyes, at constant intraocular pressure of 15 mmHg. The cornea air puff deformation was modeled using finite elements, and hyperelastic material para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…We have recently shown that it is possible to reconstruct corneal inherent mechanical parameters from corneal deformation imaging using inverse optimization. 6 In a recent study, Bekesi et al 22 demonstrated the validation of this technique on hydrogel model corneas and porcine corneas. Inherent material parameters were reconstructed from air puff deformation imaging and inverse optimization modeling that matched those obtained on the same samples using uniaxial extensiometry.…”
mentioning
confidence: 99%
“…We have recently shown that it is possible to reconstruct corneal inherent mechanical parameters from corneal deformation imaging using inverse optimization. 6 In a recent study, Bekesi et al 22 demonstrated the validation of this technique on hydrogel model corneas and porcine corneas. Inherent material parameters were reconstructed from air puff deformation imaging and inverse optimization modeling that matched those obtained on the same samples using uniaxial extensiometry.…”
mentioning
confidence: 99%
“…CXL enabled microstructural changes of the corneas. The collagen architecture modified by CXL affects both viscous and elastic properties of the cornea although decoupling the impact of those both trends can be hard . Proper interpretation of the results of CXL experiment can be done when corneal thinning is taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…A high degree of interest in corneal biomechanics has driven the development of multiple measuring devices using various approaches. Devices for measuring corneal biomechanical properties have evolved from conventional stress-strain measuring instruments (i.e., uniaxial tensile test[ 37 ]) and inflation tests[ 38 ] to commercially available air-puff systems (i.e., Ocular Response Analyzer, ORA; Reichert, Depew, New York[ 39 ]; and Corneal Visualization Scheimpflug imaging, Corvis ST; Oculus, Wetzlar, Germany[ 40 ]); more recent devices, still under development, include optical coherence elastography (OCE)[ 41 ], Brillouin microscopy[ 42 ], ultrasound indentation[ 28 ], and corneal indentation[ 29 , 43 ]. Although the uniaxial tensile test is the gold standard in mechanical engineering, measuring corneal biomechanics using this technique is difficult, because the cornea is anisotropic, highly curved, and hydrated; furthermore, measurement along a single axis may not represent corneal biomechanics as a whole, and stretching the cornea during the measurement may disrupt the distribution of its collagen fibrils[ 44 ].…”
Section: Discussionmentioning
confidence: 99%